Knowledge, Attitudes, and Barriers of Blood Donation among Students of Soran Technical College: A Cross-Sectional Study - Arazoo Issa Tahir; Sarud Manaf Ahmed; Magroom Esmail Seniar (Hawler Medical University, 2023)
Background: Safe and effective blood transfusion is a vital component in improving health and preventing the spread of blood-borne diseases worldwide. The current study aimed to assess knowledge, attitudes, and barriers toward blood donation among Soran Technical College students. Methods: A cross-sectional study was conducted from 25th February 2022 to 7th May 2022. A non-probability convenience sampling method included 200 students; it was divided into medical and non-medical students. A self-administered questionnaire with closed-ended questions was used to collect information concerning socio-demographic characteristics, knowledge, attitude, and practice regarding blood donation. Results: More than half of the study samples (59.5%) were within the age group of less than 20 years. The majority (68%) were female. And nearly half of the students came from an urban area. The majority of respondents (90.5%) had a fair level of knowledge, while 7% had good knowledge of blood donation. However, 59% of the students had a positive attitude toward blood donation. The most common motivators that encouraged blood donors were 72.5% getting subsidies and vacations, and 71% getting free laboratory examinations. Common barriers for blood donors were worried about sanitation and getting infectious diseases, and the side effects (58.7%) and (54.5%), respectively. Conclusion: Despite most of the students having a favorable attitude toward blood donation but unexpectedly having a fair level of knowledge, the major barrier perceived by students was fear of acquiring an infectious disease.